Prevalence of extra-pancreatic cysts in patients with cystic pancreatic lesions detected by endoscopic ultrasound - Bektas, Mehmet (Endosc Ultrasound, 2015)
BACKGROUND AND OBJECTIVES: Extra-pancreatic cysts (EPCs) are incidentally found in patients with pancreatic cystic lesions (PCLs). The aim of this study is to find the prevalence of concurrent EPC in patients with PCLs, investigate associations with neoplastic lesions, and compare the prevalence of EPC to a control population. MATERIALS AND METHODS: A retrospective study of patients who underwent endoscopic ultrasound (EUS) over a 3-year period. The study group consisted of patients with PCLs. The control group included equal number of matched (age and sex) patients who had undergone EUS for reasons other than evaluation of PCLs. All patients had undergone computed tomography (CT) that was reviewed for EPCs. RESULTS: A total of 191 patients were found to have PCLs. One patient with Von Hippel-Lindau (VHL) disease was excluded. Majority of the patients were female (60%); most PCLs were solitary (68.9%), unilocular (56.8%), predominantly located in the head of the pancreas (37.4%); and mean PCL diameter was 28.12 ± 18.4mm. EUS-guided fine-needle aspiration (FNA) was performed in 171 (90%) patients with 73 (42.7%) PCLs demonstrating cysts with benign epithelial cells, 37 (21.6%) mucinous cysts, 18 (10.5%) mucinous adenocarcinomas, 11 (6.4%) neuroendocrine tumors, nine intraductal papillary mucinous cystic neoplasms (IPMNs), six pseudocysts, five serous cyst adenomas (SCAs), and five with inadequate sampling. An EPC was observed in 97 of 190 (51.18%) patients with PCLs and in 67 of 190 (35.3%) controls (P < 0.001). The distribution of EPCs in PCL patients and controls (n = 190) were 32.1% vs. 15.8% (P < 0.001) for liver cysts, 30.0% vs. 20.5% (P = 0.04) for renal cysts, and 3.7% vs. 1.6% (P = 0.34) for cysts in other organs. Mean liver cyst diameter (15.6 mm vs. 10.1 mm, P = 0.23) and renal cyst diameter (20.4 mm vs. 20.1 mm, P = 0.95) were not statistically different in PCL patients compared to controls. Multivariate analysis demonstrated that among patients with PCLs, EPCs increased with age (mean age 69.6 vs. 62.4 years, P ≤ 0.001, odds ratio (OR) 1.06, 95% confidence interval (CI) 1.03, 1.09), and male gender was associated with higher chance of finding renal cysts (OR 2.17, P = 0.021, 95% CI 1.13, 4.19). There was no association between FNA result and prevalence or type of EPC. CONCLUSION: The prevalence of EPCs in patients with PCLs was significantly higher than in a matched control group. Among patients with PCLs, a liver cyst is the most common EPC. Increasing age is associated with higher prevalence of EPCs.